The Effect of Tax Understanding and Tax Sanctions on Taxpayer Compliance at KPP Pratama Ciawi (A Case Study on Micro, Small, and Medium Enterprises in Ciomas District) - Lukmanul Hakim; Mahwiyah Mahwiyah; Deswita Puji Lestari (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the effect of tax understanding and tax sanctions on taxpayer compliance among Micro, Small, and Medium Enterprises (MSMEs) in the working area of KPP Pratama Ciawi, particularly in Ciomas District. Although the relationship between taxation knowledge and taxpayer compliance has been widely investigated, empirical inconsistencies regarding the effectiveness of tax sanctions among MSMEs remain unresolved, especially within regional tax office contexts characterized by limited taxation literacy and administrative capability. This study therefore contributes to the literature by examining the interaction between voluntary compliance factors and enforcement mechanisms among MSME taxpayers. A quantitative approach was employed using purposive sampling techniques involving 80 MSME taxpayers. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 29. The results indicate that tax understanding has a positive and significant effect on taxpayer compliance (β = 0.353; p = 0.036), while tax sanctions demonstrate a stronger positive effect (β = 0.681; p < 0.001). Simultaneously, both variables significantly influence taxpayer compliance with an explanatory power of 65.3%. These findings confirm that taxpayer compliance among MSMEs is influenced by both voluntary awareness and enforcement-based compliance mechanisms. The study strengthens the Theory of Planned Behavior and the Slippery Slope Framework by demonstrating that compliance behavior within MSMEs is shaped not only by taxation knowledge but also by perceptions of sanction enforcement.